Research progress on linear IgA bullous dermatosis - Mei WU; Deliang LI; Xinxin SITU; Guoli LI; Guangwen YIN (Pifu-xingbing zhenliaoxue zazhi, 2023)
Linear IgA bullous dermatosis (LABD) is a rare autoimmune subepidermal blistering skin disease, manifested by erythematous plaques covered by circular blisters in a pattern of "string of pearls". Immune dysregulation and genetic factors are implicated in the onset of LABD. The pathogenesis includes abnormal deposition of IgA antibodies in the basement membrane zone and abnormal immune response. Although the pathological characteristics are atypical, direct immunofluorescence shows deposition of linear IgA antibody at the basement membrane zone. Advances in molecular biology and immunology offer new possibilities for enhancing precise diagnosis. Personalized treatment has become pivotal, while topical steroids and antihistamines are suitable for mild cases. Severe cases may require systemic immunosuppressants or even biologics. This review aims to summarize the latest research advances in LABD, including epidemiological features, pathogenesis, diagnostic and therapeutic strategies, and to provide an outlook on future research directions.